2020
DOI: 10.1016/j.heliyon.2020.e04407
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness assessment in Goalball: A scoping review of the literature

Abstract: Background Goalball is a Paralympic sport for visually impaired athletes. Although it is widely practiced, a great variety of tests are adopted to evaluate athletes' physical fitness. Therefore, the objective was to identify the physical fitness tests adopted in this sport to find the common aspects between them and, eventually, to propose a standard operating procedure. Methods The Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 18 publications
0
20
0
3
Order By: Relevance
“…It has been reported that postoperative traumatic stress, reduced nutrient intake and long-term bed rest are important causes of POF [13,33,34]. For PA patients, the surgical method of transsphenoidal approach is far less traumatic than craniotomy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that postoperative traumatic stress, reduced nutrient intake and long-term bed rest are important causes of POF [13,33,34]. For PA patients, the surgical method of transsphenoidal approach is far less traumatic than craniotomy.…”
Section: Discussionmentioning
confidence: 99%
“…This Special Issue bridging the gap between science and practice in the promotion of exercise and health and in the scientific assessment, study, and understanding of sports performance, sports injury prevention and treatment, exercise for health as non-surgical and nonpharmacological treatments, rehabilitation techniques, adapted physical activity, drugs in sport, and recommendations for training and nutrition. This Special issue comprises 3 review articles and 16 original research publications from a number of Sports Medicine and Sciences researchers [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Taken together, these articles are…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…This Special issue comprises 3 review articles and 16 original research publications from a number of Sports Medicine and Movement Sciences researchers [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Taken together, these articles are geared toward the advancement of our understanding Sports Medicine and Movement Sciences arena, including: Cognitive function; Brain health; Gait analysis; Biomechanics; Health sciences; Physiology; Physical activity; Occupational health; Musculoskeletal system; Evidence-based medicine; Aerobic threshold; Anaerobic threshold; Maximal oxygen uptake; Neuroscience; Exercise; Physical Activity; Balance; Metastability; Neuromuscular control; Prevention; Rehabilitation; Health Promotion; Anatomy; Health Technology; Three-dimensional motion analysis; Reliability; knee injury; Athletic pubalgia; Cardiology; Women's Health; Female athletes; Applied psychology; Clinical psychology; Paralympic sport; Goalball; Soccer; Cognitive psychology; Quality of life; Disability; Regenerative medicine; Osteoarthritis; Virtual reality; Sensorimotor control; Sports injury prevention; Epidemiology; Public health; Psychology; COVID-19; Pandemic; Quarantine; Home based exercise; IPAQ-SF; Psychological well-being; PGWBI; Nerve injury; Nerve regeneration; Therapeutic exercise; Wearable technologies; Sprint initiation; Step technique; Multi-directional movement; Novel training environments and digital devices; Adherence; Breast cancer; Lifestyle; Public Health and Digital Epidemiology.…”
mentioning
confidence: 99%
“…Research, Society and Development, v. 9, n. 10, e9079109306, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.9306 6 Nessa linha de raciocínio, uma vez reconhecido que a força é um importante parâmetro para a prática de diversos esportes, e que o Golbol é uma prática paralímpica de expressão entre os deficientes visuais (Petrigna et al, 2020), compreende-se que o conhecimento acerca dos aspectos motores dos praticantes, sejam a respeito da força de membros superiores ou demais aspectos, podem fornecer informações relevantes para a prescrição de treinamentos que venham favorecer o desempenho e o rendimento dos atletas na modalidade, bem como proporcionar informações científicas que possam contribuir para a criação de metodologias específicas de treinamento esportivo adaptado à modalidade e à deficiência dos atletas. Dito isso, e em face da carência de estudos com pessoas deficientes (Vigário et al;, em especial esportistas e praticantes da modalidade de Golbol, esse estudo teve como como objetivo avaliar os níveis de força de membros superiores em pessoas com deficiência visual adeptas a prática esportiva de Golbol.…”
Section: Diante Dessa Variedade De Atividades Motrizes Tem Ganhado Dunclassified